Determinants Of Malaysian Household Expenditures On Freshfish, Shellfish, And Processed Fish. - Tan, Andrew,Khee Guan; Lee, Helen,Siew Heng (2005)
The censored Tobit model is used to examine how socio-demographic factors affect the demand for seafood products in Malaysia. Results of the study indicate that households with matured and retired individuals appear to be more health-conscious and are more inclined to increase the frequency with which freshfish appears in the household's diet compared to their younger counterparts.